Impairment-aware optimization strategies to dimension optical transport networks with minimal regeneration requirements - Mendes, Ricardo (2016)
Abstract—Physical impairments restrain the maximum length a signal can travel without regeneration. The quality of a signal in optical wavelength division multiplexing (WDM) networks must thus be restored with opto-electro-optical (OEO) regeneration in order to reach its destination. As OEO regenerators are costly devices, sparse deployment using routing optimization is the key to reduce the network cost. This paper tackles the problem of impairment aware routing and wavelength assignment with regeneration placement (RWARP), considering capacity constraints, while focusing on minimizing the number of regenerators. We will firstly, extend an Integer Linear Programming (ILP) formulation for the RWARP problem which provides, when feasible, an optimal solution, and secondly, propose an efficient heuristic. Results show that the heuristic provides satisfactory results, optimal for small problems, in a fraction of the ILP execution time.